2021
DOI: 10.3389/fpsyt.2021.623143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Metabolite Variability in One-Carbon Metabolism Applied to an Insulin Resistance Model in Patients With Schizophrenia Receiving Atypical Antipsychotics

Abstract: Background: Patients with schizophrenia are at high risk of pre-mature mortality due to cardiovascular disease (CVD). Our group has completed studies in pharmacogenomics and metabolomics that have independently identified perturbations in one-carbon metabolism as associated with risk factors for CVD in this patient population. Therefore, this study aimed to use genetic and metabolomic data to determine the relationship between folate pharmacogenomics, one-carbon metabolites, and insulin resistance as measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It shows that fasting blood glucose and triglyceride levels are risk factors for obesity. Ward et al [ 44 ] have found that the incidence of metabolic syndrome in schizophrenia is higher than that of the normal population, which may be related to the use of atypical antipsychotics. Chen et al [ 45 47 ] have found that typical antipsychotics and atypical antipsychotics can also affect the glucose and lipid metabolism of patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that fasting blood glucose and triglyceride levels are risk factors for obesity. Ward et al [ 44 ] have found that the incidence of metabolic syndrome in schizophrenia is higher than that of the normal population, which may be related to the use of atypical antipsychotics. Chen et al [ 45 47 ] have found that typical antipsychotics and atypical antipsychotics can also affect the glucose and lipid metabolism of patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR 677T carriers in Ellingrod’s study [ 16 ] and MTHFR 1298C carriers in van Winkel’s study [ 22 ] were reported to have higher risks of metabolic syndrome. Additionally, carriers with MTHFR 677T or MTHFR 1298C allele had a higher level of insulin resistance [ 23 ]. By contrast, the MTHFR 677T allele seemed to be protective against metabolic syndrome in Roffeei’s study on Asian patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%